Paradoxical Sensitivity to Sub-threshold Asynchronies in Schizophrenia: A Behavioral and EEG Approach. Issue 1 (26th March 2021) - Marques-Carneiro, José Eduardo; Krieg, Julien; Duval, Céline Z; Schwitzer, Thomas; Giersch, Anne
Abstract: The flow of consciousness is disrupted and disorganized in schizophrenia. We explore the hypothesis that this disruption is related to asynchronies not being predicted in advance and standing out instead of being integrated in the flow of events. We recorded EEG continuously during a simultaneity/asynchrony discrimination task, in which subjects decide whether 2 squares are shown simultaneously or with an asynchrony (asynchronies were between 24 and 96 ms). Behavioral data was obtained in 32 patients with schizophrenia and 27 matched controls, and EEG was recorded in a subset of 17 patients vs 15 controls. Two results suggested a lack of asynchrony prediction in patients. Behavioral difficulties at detecting asynchronies increased in patients with schizophrenia relative to controls after a detection of simultaneity, and this effect was correlated with clinical disorganization. Desynchronization of alpha activity observed before the beginning of a trial was larger after asynchronous than simultaneous responses in controls, but not in patients. EEG signals additionally suggested abnormal sensitivity to short asynchronies in patients. The amplitude of early signals around 180 ms after the first square abnormally increased in patients for short asynchronies relative to perfect simultaneity, whereas EEG signals at parietal regions decreased in amplitude in patients relative to controls, in the 400–600 ms interval after the first square. These results reinforce the hypothesis of time prediction and sequencing impairments at the sub-second level and may provide an explanation for the disruption of the patients' consciousness flow.